Pengaruh karakteristik CEO terhadap kinerja bagian keuangan (akuntan) Perusahan - Adanan Silaban; Manatap Berliana Lumban Gaol (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The company is one of the sectors that can be used to improve the Indonesian economy. Unfortunately, not all companies are in good health, especially in the financial sector. In fact, finance is important for the sustainability of the company's operations. The company's finances are held by an accountant who is under the authority of the CEO. For this reason, researchers want to conduct research on "The Effect of CEO Characteristics on the Performance of the Company's Finance (Accountant) Division". The purpose of this research is to find out more about whether or not the CEO's influence on the good or bad performance of accountants will have an impact on the company. The method used is a descriptive quantitative method with data collection techniques through interviews, observations, questionnaires and documentation of 20 companies listed on the Indonesia Stock Exchange in 2019-2022 which were selected by random sampling. The results show that CEO characteristics have an influence on company performance in detail: age has an effect of 60%, CEO tenure has an effect on 75%, educational background has an effect of 95% and CEO traits 25%.